Comparing serum ferritin levels during COVID-19 infection and recovery period in pediatric patients with transfusion-dependent thalassemia, a single-center study - Marhaeni, Wulandewi; Felicia, Fabiola Vania; Sumadi Jap, Arvin Leonard; Hartoyo, Edi; Andayani, Pudji (Frontiers in Medicine, 2023)
Background: Ferritin is an inflammatory biomarker that has been recognized as a predictor of severity among COVID-19 patients. Studies have shown higher levels of ferritin in patients with COVID-19 than in healthy children. Patients with transfusion-dependent thalassemia (TDT) basically have high ferritin level due to iron overload whether any significant changes in serum ferritin level in these patients is associated with COVID-19 infection. Objective: To evaluate ferritin levels in transfusion-dependent thalassemia with COVID-19 before, during, and after the course of infection. Methods: This retrospective study enrolled all transfusion-dependent thalassemia children with COVID-19 infection that were hospitalized in Ulin General Hospital Banjarmasin during the COVID-19 pandemic (March 2020 to June 2022). Data were collected from medical records. Results: There were 14 patients included in this study, 5 patients had mild symptoms and 9 patients were asymptomatic. The mean of hemoglobin level upon admission was 8.1 + 3 g/dl and serum ferritin level was 5148.5 + 2651.8 mg/dl. The average serum ferritin level during COVID-19 infection was 1213.94 mg/dl higher than before infection and 884.43 mg/dl lower after infection. We found no association of increasing serum ferritin with patients’ symptoms (p = 0.27). The severity of anemia also was not correlated with the presentation of COVID-19 infection (p = 0.902). Conclusion: Serum ferritin levels in TDT children may not reflect disease severity or predict poor outcomes during COVID-19 infection. However, the presence of other co-morbid conditions/confounders warrants cautious interpretation.